The paradigms of the Hermeneutics in the peruvian constitutional jurisdiction - Ahomed Chávez, Omar Abraham (2018)
The present work explains the principles, methods and rules of hermeneutics that judges must use in cases of violation of constitutional rights. Likewise, it specifically analyzes the practical application of these rules of  interpretation in the precedent case of the Constitutional Court of Peru.